Reflection on environmental awareness for school management - Mohamad, Mimi Mohaffyza; Ibrahim, Badaruddin; Lai, Chee Sern; Ahmad, A.; Md Nasir, A.N. (Innovare Academics Sciences PVT. LTD, 2020)
The purpose of this study is to analyze the perceptions of the administrators in terms of their environmental awareness. This study is based on their knowledge, attitude and behavior. Besides, this study also aimed to determine the differences of environmental awareness based on race and gender, and to identify the relationship between knowledge, attitude and behavior towards environmental awareness among the administrators. This study involved 50 administrators in one of the districts in Johor. The survey method was used in data collection, and the questionnaire developed by other researchers was modified to match with the characteristics of the present research subjects. Data were analyzed using descriptive and inferential statistics. The result showed that the environmental awareness in terms of attitude was at a high level, whereas the awareness from the aspects of knowledge and behavior were at a moderate level. In addition, it has been found that there was no significant difference in environmental awareness between gender-based on knowledge, attitude and behavior. The result also indicated that there was no significant difference in environmental awareness among races in knowledge. Also no significant difference was discovered in terms of attitude and behavior. Apart from that, the correlation analysis revealed that the awareness of attitude and behavior were positively correlated. On the contrary, the awareness of knowledge was negatively correlated with attitude as well as behavior. In conclusion, the present findings demonstrate that the administrator aware of the importance of environmental conservation.